Changes in Within-Shoot Carbon Partitioning in Pinot Noir Grapevines Subjected to Early Basal Leaf Removal - Frioni, Tommaso; Acimovic, Dana; Tombesi, Sergio; Sivilotti, Paolo; Palliotti, Alberto; Poni, Stefano; Sabbatini, Paolo (Frontiers in Plant Science, 2018)
Early leaf removal significantly alters the source-sink balance within grapevine shoots, leading to a reduction in fruit set. However, no research has previously examined the conditions controlling this process in terms of carbon allocation among major sink organs following defoliation. In this study, the impact of defoliation at bloom on the distribution dynamics of leaf assimilates among clusters and growing shoot apices was investigated on Vitis vinifera, cv. Pinot noir, grown in Michigan, a cool climate viticultural region. Three levels of defoliation: no leaves removed (LR-0); six leaves removed from six basal nodes (LR-6); and ten leaves removed from ten basal nodes (LR-10), were imposed at full bloom. A 13C pulsing was performed one week after the treatment application to the defoliated shoots. Single leaf gas exchange (Pn), diurnal changes of the leaf net CO2 assimilation rate, carbon distribution, fruit-set, yield and fruit composition were measured. Higher Pn was recorded in diurnal measurements of gas exchange in leaf removal (LR) treatments compared to LR-0. The shoot apex of LR-10 experienced the highest 13C allocation (%) after 3 and 7 days following the carbon pulsing. LR-10 had lower percentage of 13C allocated to clusters, which decreased fruit set by 60%, compared to the control, and enhanced the concentration of phenolic compounds in fruit. Alteration of carbon portioning among shoot sink organs indicated that an increasing severity of leaf removal significantly reduced fruit set, and was linearly correlated to shoot apex sink strength, which occurred at the expense of the cluster.